Improved BER based on intensity noise alleviation using developed detection technique for incoherent SAC-OCDMA systems - Hamza Mohammed Ridha, Al-Khafaji; Syed Alwee Aljunid, Syed Junid, Prof. Dr.; Hilal Adnan, Fadhil, Dr. (Taylor and Francis Group, LLC., 2013)
Link to publisher's homepage at http://www.tandfonline.com/